Pin Tract Infection Following Correction of Charcot Foot With Static Circular Fixation. (November 2015) - Finkler, Elissa S.; Kasia, Christopher; Kroin, Ellen; Davidson-Bell, Victoria; Schiff, Adam P.; Pinzur, Michael S.
Background: The traditional nonsurgical accommodative treatment for diabetes-associated Charcot foot arthropathy has been unsuccessful in improving the quality of life in affected individuals. This has led to the growing interest in surgical correction of the acquired deformity with either "super construct" internal fixation implants or fine-wire static circular external fixation. The use of static circular external fixation without implants has been demonstrated to achieve high rates of deformity correction with low complication rates. The goal of this investigation was to assess the risk of pin site infection in this high-risk patient population. Methods: Over an 11-year period, 283 consecutive diabetic patients underwent single-stage correction of Charcot foot deformity with static fine-wire circular external fixation and no internal fixation devices. Pin care was minimal. Results: Fifty-nine (20.8%) patients developed clinical signs of pin tract infection in at least 1 pin site. Forty-nine occurred in patients undergoing surgical correction of deformity in the foot. Eight occurred in patients undergoing surgical correction at the ankle level and 2 in patients undergoing complex reconstruction for combined foot and ankle deformity. Higher rates of pin site infections were observed in patients with osteomyelitis present at the time of surgery (25.6%) as compared with patients without evidence of infection (17.8%), although the difference was not statistically significant ( P = .1184). There was no correlation between body mass index and pin site infection ( P = .288). There was a statistically significant trend ( P < .05) for higher rates of pin site infection in patients with elevated hemoglobin A1C levels. Erythema and drainage resolved in all patients with local pin care and empiric oral antibiotic therapy. None of the wires were removed prematurely, and all infections resolved following removal of the circular external fixator at the scheduled time for removal. Conclusions: Pin site infection was common following surgical correction of the acquired deformity associated with Charcot foot. These acquired pin site infections were a nuisance but did not appear to add permanent morbidity or require additional surgery to resolve. Level of Evidence: Level IV, retrospective case series.